Proportional-Derivative Observer-Based Backstepping Control for an Underwater Manipulator. (29th November 2011) - Santhakumar, M.
Abstract : This paper investigates the performance of a new robust tracking control on the basis of proportional-derivative observer-based backstepping control applied on a three degrees of freedom underwater spatial manipulator. Hydrodynamic forces and moments such as added mass effects, damping effects, and restoring effects can be large and have a significant effect on the dynamic performance of the underwater manipulator. In this paper, a detailed closed-form dynamic model is derived using the recursive Newton-Euler algorithm, which extended to include the most significant hydrodynamic effects. In the dynamic modeling and simulation, the actuator and sensor dynamics of the system are also incorporated. The effectiveness of the proposed control scheme is demonstrated using numerical simulations along with comparative study between conventional proportional-integral-derivative (PID) controls. The results are confirmed that the actual states of joint trajectories of the underwater manipulator asymptotically follow the desired trajectories defined by the reference model even though the system is subjected to external disturbances and parameter uncertainties. Also, stability of the proposed (model reference control) control scheme is analyzed.